2023
DOI: 10.3389/fmicb.2022.1103836
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate producers, “The Sentinel of Gut”: Their intestinal significance with and beyond butyrate, and prospective use as microbial therapeutics

Abstract: Gut-microbial butyrate is a short-chain fatty acid (SCFA) of significant physiological importance than the other major SCFAs (acetate and propionate). Most butyrate producers belong to the Clostridium cluster of the phylum Firmicutes, such as Faecalibacterium, Roseburia, Eubacterium, Anaerostipes, Coprococcus, Subdoligranulum, and Anaerobutyricum. They metabolize carbohydrates via the butyryl-CoA: acetate CoA-transferase pathway and butyrate kinase terminal enzymes to produce most of butyrate. Although, in min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(81 citation statements)
references
References 173 publications
2
48
0
Order By: Relevance
“…This could be attributed to donor 2 having a higher relative abundance of butyrate-producing bacteria such as Faecalibacterium prausnitizii OTU217, Anaerostipes hadrus OTU41, Blautia OTU254, Eubacterium rectale ATCC33656 OTU133, Ruminococcus torques group OTU48, and Ruminococcus N15.MGS57 OTU112 (Figure ). In contrast, donor 1 had a high relative abundance of Prevotella , which accounted for over 50% of the initial microbiota composition (Figure ) and is known as a propionate-producing bacterium. Therefore, donor 1 exhibited higher propionate production than butyrate.…”
Section: Resultsmentioning
confidence: 99%
“…This could be attributed to donor 2 having a higher relative abundance of butyrate-producing bacteria such as Faecalibacterium prausnitizii OTU217, Anaerostipes hadrus OTU41, Blautia OTU254, Eubacterium rectale ATCC33656 OTU133, Ruminococcus torques group OTU48, and Ruminococcus N15.MGS57 OTU112 (Figure ). In contrast, donor 1 had a high relative abundance of Prevotella , which accounted for over 50% of the initial microbiota composition (Figure ) and is known as a propionate-producing bacterium. Therefore, donor 1 exhibited higher propionate production than butyrate.…”
Section: Resultsmentioning
confidence: 99%
“…Numbers of studies have investigated the antitumorigenic role of bacteria that are considered pathogens Anaerostipes, which is a butyrate producer, has been found to be associated with various ailments . A study reported that Vibrio could generate a cytotoxin termed motility-associated killing factor A (MakA).…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] Acetylene and propionate degradation can also regulate the production of SCFAs. 50 Amino acid metabolism, 51 such as lysine synthesis and glutamate degradation, and pathways under fatty acid metabolism 52,53 help produce SCFAs, provide energy, and regulate intestinal immune function. Butyric acid growth provides the energy required to produce colonic mucus, and Akkermansia stimulates the production and metabolism of colonic mucus.…”
Section: Food and Function Papermentioning
confidence: 99%